Diseño del plan de validación de los equipos piloto en la zona centro de transformación y adecuación (CETA) del centro de procesos e innovación para la industria sostenible (CEPIIS) de la Fundación Universidad de América. (2023)
The Universidad de América Foundation in 2016 launched the most ambitious engineering project to date in the institution, for the industrial practice of production, research and experimentation projects called: (CEPIIS) for its acronym Center for processes and innovation for the sustainable industry which has three fundamental areas: a process plant, a water treatment plant and a weather station. The project: Design of the Validation Plan for pilot equipment of the transformation and adaptation center (CETA) of (CEPIIS) focused on the process plant, specifically in the CETA area, an area that includes: Reactor bank and evaporator train.